Aligning Data Governance with the Social Contract for Data to Promote Value, Trust, and Equity - World Bank (Washington, DC: World Bank, 2022)
In a world where data are becoming an integral part of our lives, data governance has become essential to support the production, use and reuse of data in a safe, ethical, and secure manner. In effect, data governance enforces the social contract around data, by applying the principles of trust, value, and equity. This primer provides an overview of the different elements of a data governance framework as discussed in the World Development Report 2021, Data for Better Lives. The implementation of the different elements of the framework will be specific to a country context, informed by local norms, laws, and culture. Using this framework, a series of briefs accompanying this primer, will explore and review the data governance landscape in different regions with a view to facilitating the region’s pathway to a green, resilient, and inclusive recovery.